PERANCANGAN SISTEM PENJURIAN BAGI FEDERASI OLAHRAGA BARONGSAI INDONESIA (FOBI) MAKASSAR - Pieter Wonggianto; Syaiful Rahman; Junaedy (JTRISTE, 2018)
This research aims to design the application of lion barra cage system for Indonesia Lion dance sports federation of Makassar on Android smart phone and test the application made whether it can be used to conduct the lion barraque process. The literature study was conducted to collect information related to research such as the assessment of the lion dance game, android and java programming. To design the presence process, the author uses UML modeling language which consists of use case diagram and activity diagram. In its implementation, the Java programming language is used to create server and application presensi on android smartphone. The results of the analysis are designed using UML modeling language which consists of use case diagram and activity diagram. Test results above the Android platform show that the judging system created can be used to perform a lenght barging system, where a side judge residing in the match field can assess the team Is playing through his android device. So this can help the judge side to do the assessment without having to return to the jury table.